An input-output analysis of unit labour cost developments of the German manufacturing sector since the mid-1990s - Nora Albu; Heike Joebges; Rudolf Zwiener (Journal for Labour Market Research, 2022)
According to empirical studies, a statistically significant factor for German exports success is high cost (or price) competitiveness. Studies by Deutsche Bundesbank recommend correcting the nominal effective exchange rate by broad cost (or price) indicators (Deutsche Bundesbank, 1998, 2016a). This would call for total economy unit labour costs. In contrast to these findings, Dustmann et al. (2014) suggest using refined unit labour costs for the exporting manufacturing sector only, corrected for inputs from other sectors and from abroad in an Input-Output (IO) analysis framework. According to these authors' novel calculation, the export-oriented manufacturing sector of Germany experienced a decrease in unit labour costs by 25% between the mid-1990s and 2007. We try to replicate their findings. Following standard approaches in calculating sectoral unit labours costs, correcting for inputs from other sectors and from abroad, and using consistent input-output data from the Federal Statistical Office and from the World Input-Output Database, nominal unit labour costs of the manufacturing sector did not decrease over the period of analysis, and developed similarly to total unit labour costs. The similarity to total economy costs is also confirmed for a more recent period. In contrast to these authors' claim, our findings are in line with recommendations of Deutsche Bundesbank for using total economy unit labour costs.
Keywords: C67; F16; 330; Input-output analysis; German exports; Cost competitiveness; Unit labour costs; Real effective exchange rate; Manufacturing sector; Wage costs; Outsourcing